Religion and Religious Diversity within Education in a Social Pedagogical Context in Times of Crisis: Can Religious Education Contribute to Community Cohesion? - Koukounaras-Liagkis, Marios (The International Journal of Social Pedagogy, 2015)
In this article the author argues that the teaching of religion(s) in education, in a social pedagogical context, can encourage community cohesion especially when, during the current harsh crisis, the need for cohesion seems to be of paramount importance in enabling seemingly insurmountable problems to be overcome. At the same time minorities become vulnerable and diversity, a matter of high priority, comes to the fore. The author reviews evidence of research on the effect of educational intervention within Religious Education on student attitudes toward religious diversity. He proposes that constructivist methodology, using theatre/drama as a means of Religious Education, could give people the choice to be critical religious believers and active members in a society applyingthe fundamental social pedagogical principle of tolerance to and respect for the ‘other’.